Fairness Aspect in the Paroan System in the Mangar Society - Martoyo Martoyo; Abdul Jabbar (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2023)
This research was conducted on the Mangar society who have a system of cooperation in the form of